Cardiovascular Disease Profile of the Oldest Adults in Rural South Africa: Data from the HAALSI Study (Health and Aging in Africa: Longitudinal Studies of INDEPTH Communities). Issue 11 (12th October 2018) - Jardim, Thiago Veiga; Witham, Miles D.; Abrahams‐Gessel, Shafika; Gómez‐Olivé, F. Xavier; Tollman, Stephen; Berkman, Lisa; Gaziano, Thomas A.
Abstract : Objectives: To characterize the cardiovascular disease (CVD) profile of individuals aged 80 and older in rural South Africa. Design: First wave of population‐based longitudinal cohort. Setting: Agincourt subdistrict (Mpumalanga Province) in rural South Africa. Participants: Adults residents (N = 5, 059). Measurements: In‐person interviews were conducted to obtain social, behavioral, economic, and clinical data. Prevalence of hypertension, diabetes, dyslipidemia, high waist‐to‐hip ratio, overweight and obesity, high‐risk high‐sensitivity C‐reactive protein, smoking, stroke, myocardial infarction, angina pectoris, and heart failure in individuals younger than 65, aged 65 to 79, and aged 80 and older were compared. Associations between self‐reported treatments and determinants of hypertension treatment in those aged 80 and older were assessed using multivariable regression. Results: Of 5, 059 individuals included, 549 (10.8%) were aged 80 and older, and their CVD prevalence was 17.9% (stroke 3.8%, myocardial infarction 0.5%, angina pectoris 13.5%, heart failure 0.7%). Hypertension prevalence in this group was 73.8%, and along with angina pectoris, it increased with age (p<.001), whereas overweight and obesity (46.4%), dyslipidemia (39.1%), and smoking prevalences (3.1%) decreased (p<.001). Hypertension treatment was significantly associated with being aged 80 and older (odds ratio (OR)=1.48; 95% confidence interval (CI)=1.14–1.92, p=.003). Male sex (OR=0.73, 95% CI=0.66–0.88, p=.001), being an immigrant (OR=0.80, 95% CI=0.65–0.98; p=.03), higher socioeconomic status (OR=1.28, 95% CI=1.06–1.53, p=.009), and higher depression score (OR=1.12, 95% CI=1.05–1.19, p<.001) were associated with hypertension treatment in those aged 80 and older. Conclusion: This is the first study to characterize the CVD profile of individuals aged 80 and older in sub‐Saharan Africa and provides baseline data for comparison with future studies in this rapidly growing age group.J Am Geriatr Soc 66:2151–2157, 2018.